Real estate prices and bank risk-taking in Japan. Issue 1 (2nd January 2021) - Wang, Rui; Luo, Hang (Robin)
Abstract: This study examines the impact of real estate prices on bank risk-taking using a sample of 133 commercial banks in Japan from 2007 to 2016. Having controlled for other bank-risk determinants, we find that house price growth, house price deviation, and its cyclicality have significant positive (negative) impacts on bank risk-taking (stability). This finding is robust to using different bank risk measures and various econometric methods. Moreover, rising property prices decrease bank stability mainly by weakening bank capitalization and increasing banks' volatility of returns. In addition, we find that the adverse effect of rising house prices on the stability of a bank becomes more pronounced when house prices rise abnormally and when the market structure reflects a monopoly. Our results also indicate that increasing house prices exacerbate the destructive effects of abnormal credit growth on bank stability.